2023
DOI: 10.1177/21651434221146470
|View full text |Cite|
|
Sign up to set email alerts
|

The Goal Setting Challenge App: Impact on Transition Goal Attainment Outcomes of Students With Disabilities

Abstract: Promoting self-determination is essential to effective transition services and supports. The Goal Setting Challenge App (GSC App) was developed to deliver self-determination instruction via technology, building on the evidence-based Self-Determined Learning Model of Instruction (SDLMI). This article presents data on goal attainment outcomes for students with disabilities who participated in a small, cluster randomized controlled trial (C-RCT) of the GSC App during the 2020 to 2021 academic year and the ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…First, student attrition in both regions, but particularly the Southeast, occurred either because students stopped attending or participating in virtual instruction or participated so infrequently, they could not maintain progress in the GSC App consistent with the class implementation schedule. Although previous sensitivity analyses on student outcomes using the GSC App suggested confidence in intervention effects despite student attrition (Mazzotti et al, 2023; Shogren, Mazzotti, Hicks, et al, 2023), because unexplained attrition can bias reported effects, future research should examine how to support teachers and students in staying on track with their implementation schedules and replicate the current analyses to assess potential differences. Second, due to the compounding limitations of small sample size and 12 possible pathways across Phase 3 GSC App lessons, the average ratings of student responses to Phase 3 activities could not be adequately explored in this analysis.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…First, student attrition in both regions, but particularly the Southeast, occurred either because students stopped attending or participating in virtual instruction or participated so infrequently, they could not maintain progress in the GSC App consistent with the class implementation schedule. Although previous sensitivity analyses on student outcomes using the GSC App suggested confidence in intervention effects despite student attrition (Mazzotti et al, 2023; Shogren, Mazzotti, Hicks, et al, 2023), because unexplained attrition can bias reported effects, future research should examine how to support teachers and students in staying on track with their implementation schedules and replicate the current analyses to assess potential differences. Second, due to the compounding limitations of small sample size and 12 possible pathways across Phase 3 GSC App lessons, the average ratings of student responses to Phase 3 activities could not be adequately explored in this analysis.…”
Section: Discussionmentioning
confidence: 96%
“…The goal of these rubrics was to allow for evaluation of students’ responses to lesson activities and Student Questions and determine the degree to which responses reflected enactment of the knowledge and skills gained during the lesson, consistent with the lesson objectives. These rubrics were developed with the intent of using them to inform instructional supports (including SDLMI Educational Supports) as well as documenting students’ engagement and responsiveness as students completed each GSC App lesson, one aspect of GSC App fidelity (see Shogren, Mazzotti, Gerasimova, et al, 2023). For example, the Lesson 1, Activity 1 (aligned with Teacher Objective 1a) prompts students to type or record two of their strengths related to their selected goal area (i.e., academic skills, self-management skills, transition skills).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Goal Setting Challenge (GSC) App (Shogren & Mazzotti, 2020) was developed to build on the evidence-based SDLMI and explore the feasibility of technology-based instructional approaches to support the delivery of the SDLMI in secondary education and transition planning. The GSC App was designed to take the SDLMI format and “translate” it into a technology-based instructional format that enables the Teacher Objectives to be achieved through technology, with built-in and customizable Educational Supports, that enable students to respond to the Student Questions, based on learning needs and preferences.…”
mentioning
confidence: 99%